Dynamical evolution of anisotropies of the solar wind magnetic turbulent outer scale - Ruiz, Maria Emilia (2012)
The evolution of the turbulent properties in the solar wind, during the travel of the parcels of fluid from the Sun to the outer heliosphere still has several unanswered questions. In this work, we will present results of an study on the dynamical evolution of turbulent magnetic fluctuations in the inner heliosphere. We focused on the anisotropy of the turbulence integral scale, measured parallel and perpendicular to the direction of the local mean magnetic field, and study its evolution according to the aging of the plasma parcels observed at different heliodistances. As diagnostic tool we employed single-spacecraft correlation functions computed with observations collected by Helios 1 & 2 probes over nearly one solar cycle. Our results are consistent with driving modes with wave-vectors parallel to the direction of the local mean magnetic field near the Sun, and a progressive spectral transfer of energy to modes with perpendicular wave-vectors. Advances made in this direction, as those presented here, will contribute to our understanding of the magnetohydrodynamical turbulence and Alfvénic-wave activity for this system, and will provide a quantitative input for models of charged solar and galactic energetic particles propagation and diffusion throughout the inner heliosphere. © 2012 International Astronomical Union.